Prognostic Function of Programmed Cell Death-Ligand 1 in Esophageal Squamous Cell Carcinoma Patients Without Preoperative Therapy: A Systematic Review and Meta-Analysis - Cui, Hongxia; Li, Yarong; Li, Su; Liu, Guangxuan (Frontiers in Oncology, 2021)
Background: Studies about the correlation between the expression of PD-L1 and prognosis in ESCC patients without preoperative therapy have increased significantly, but the conclusion remains conflicting. Therefore, this study was aimed to determine the association between clinical outcomes and expression of PD-L1 in ESCC patients without preoperative therapy. Methods: We conducted a comprehensive literature search using four databases up to May 2020. Quality assessment was carried out strictly according to the Newcastle–Ottawa Quality Assessment Scale (NOS). Hazard ratios (HRs) was employed to analyze the association of PD-L1 expression with prognosis in ESCC. Furthermore, we discussed the correlation between PD-L1 and clinicopathological characteristics using odds ratios (OR) and 95% CIs. Results: 20 studies (19 publications) with 3677 patients were included in this meta-analysis. We found that the expression of PD-L1 was not related to overall survival (OS, HR: 1.16, 95% CI: 0.94 to 1.42, P = 0.16) or disease-free survival (DFS, HR: 0.85, 95% CI: 0.66 to1.10, P = 0.21) in ESCC. Furthermore, although the PD-L1 overexpression was not significantly associated with gender, degree of differentiation, TNM stage, T stage, Lymph node status, smoking or alcohol use, the merged OR demonstrated that the expression of PD-L1 was higher in older patients compared to younger patients (OR: 1.40, 95% CI: 1.07 to 1.83, P = 0.01). No obvious publication bias was observed. Conclusions: Our present study illustrated that the PD-L1 expression was not related to prognosis of ESCC patients without preoperative therapy. Notably, the PD‑L1 expression had significant association with age. As this meta-analysis had several limitations, our results need to be verified through further large-scale and prospective studies in the future.